The Influence of Financial Technology and Financial Literacy Towards Financial Inclusion in Rural Communities Padamara, Sukamulia District, East Lombok Regency - Lalu Sopian Hidayat; Lalu Hamdani Husnan (LP2M IAIN Palopo, 2026)
Despite the rapid growth of global fintech, rural Indonesia still faces a financial inclusion gap, with the national index at 75.02% but the rural index at only 70.13% (OJK, 2024). This study examines the influence of financial technology and financial literacy on financial inclusion in Padamara Village, East Lombok. Using a descriptive quantitative approach with a pre-post survey design, a population of 5,443 people was sampled with 100 respondents through purposive sampling (Slovin formula, 10% margin of error). Primary data from a Likert scale questionnaire (Pearson Product Moment validity, Cronbach's Alpha reliability >0.70) were analyzed using SPSS 27, including descriptive statistics, Lilliefors normality test, and Paired Samples T-test. The results showed a significant increase post-intervention: financial technology scores from 1.94 (low) to 3.60 (high), financial literacy from 1.94 (low) to 3.59 (good), and financial inclusion from 1.87 (low) to 3.68 (high), all with p=0.001. The conclusion proves that both factors have a positive and significant effect on financial inclusion. Practical implications recommend that the Financial Services Authority (OJK) and village governments integrate fintech-literacy education programs.